THE RELATIONSHIP BETWEEN EARLY MARRIAGE AND STUNTING INCIDENCE IN LANGKAT REGENCY - Windani, Sri; Meiliawati, Indri; Dewiwati, Tri Suci (Pena Cendekia Insani, 2025)
Stunting remains one of the major public health challenges in Indonesia, particularly in Langkat Regency, North Sumatra, where early marriage is still prevalent. This study aims to examine the relationship between maternal age at marriage and the incidence of stunting in children under five, as well as the role of women’s empowerment in prevention. A quantitative correlational descriptive design was applied with purposive sampling of 30 mothers who married before the age of 18 and had children under five years old. Data were collected using structured questionnaires and analyzed with Chi-Square tests and descriptive statistics. The results show a significant association between early marriage and child stunting, ?² (3, N = 30) = 9.090, p = 0.028, with a linear trend (p = 0.004) indicating that the older the maternal age at marriage, the lower the prevalence of stunting. At 15 years of marriage age, 75 percent of children experienced stunting, compared to 53.8 percent at 16 years, 12.5 percent at 17 years, and none at 18 years. Women’s empowerment indicators reveal that although most respondents have access to health information (93.3 percent) and routinely attend posyandu services (86.7 percent), only 23.3 percent independently make decisions regarding child health, showing limited agency despite available resources. These findings confirm that early marriage significantly increases the risk of stunting through biological immaturity, limited nutritional literacy, and reduced maternal decision-making. Women’s empowerment emerges as a strategic pathway to delay marriage, strengthen parenting, and reduce stunting prevalence. Policy recommendations include enhancing adolescent reproductive health education, improving maternal nutrition literacy, and promoting cross-sectoral collaboration between health, education, and religious affairs offices.